GEORGE WILHELM FRIEDRICH HEGEL: MORALITAS DAN STRUKTUR SOSIAL - Pranoto, David Susilo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2019)
Studying philosophy brings people to think about the meaning of life, but learning Theology brings people to understand the meaning of life. But humans also need to think about morality and social structure. The basic thinking about morality and social structure is contained in the thinking section of a philosopher named G.W.F. Hegel Therefore this article was written with the aim of critically examining Hegel's philosophy of morality and social structure from the perspective of the Bible to build a concept of morality and social structure based on the Bible of God's Word.